Genetic Diversity, Pathogenicity And Secondary Metabolites Of Fusarium Spp. Associated With Bakanae Disease Of Rice In Malaysia And Bangladesh - Husna, Asmaul (2025)
Bakanae disease is an emerging rice disease that has become a major problem in asian rice growing countries, including bangladesh and malaysia. The disease can reduce rice production by up to 30%. Fusarium fujikuroi was known to cause bakanae disease, while only a few other fusarium species were associated with it. The current population of fusarium species may not be the same as previously reported due to changes in rice varieties, climate, taxonomic tool and population migrations. Therefore, the aim of the present study was to identify and characterise the fusarium species associated with bakanae disease of rice in malaysia and bangladesh based on morphological, biological, molecular, and physiological traits. In 2019-2022, a survey for bakanae-infected plants were conducted in different rice growing areas in malaysia and bangladesh. Accordingly, fusarium isolates were isolated from bakanae-infected plants. Twelve fusarium species were morphologically and biologically identified from 210 fusarium isolates. However, based on molecular identification using tef-1α and rpb2 genes, 17 fusarium species, namely, f. Fujikuroi, f. Verticillioides, f. Proliferatum, f. Andiyazi, f. Mangiferae, f. Longipes, f. Solani, f. Oxysporum, f. Graminearum, f. Commune, f. Hainanense, f. Bubalinum, f. Pernambucanum, f. Tanahbumbuense, f. Sulawesiense, f. Flagelliforme and f. Arcuatisporum were identified. Compared to bangladesh, a broad spectrum of fusarium species associated with bakanae disease of rice was found in malaysia.